2018
DOI: 10.1111/jicd.12379
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness of oral cancer among adults in Jakarta, Indonesia

Abstract: Aim The aim of the present study was to investigate the awareness of oral cancer among adults in Jakarta, Indonesia, and explore the factors influencing it. Methods A previously‐tested questionnaire on 1000 adults in Jakarta was used in the present study. The data included sociodemographic factors and answers to assess the awareness of oral cancer, early signs and symptoms, risks factors, lifestyles, and history of dental visits. Results Only 53.2% of participants were aware of oral cancer. The level of awaren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
4
21
2
Order By: Relevance
“…The effect of different demographic and socioeconomic variables on the rate of the correct response was also investigated in previous studies. The degree of awareness to OC according to gender in previous questionnaire-based surveys showed no significant differences between males and females [26,27], which is consistent with the results of our study. Similarly, the same consistency was observed between responses of the current survey with other studies in relation to age [26,27], i.e.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of different demographic and socioeconomic variables on the rate of the correct response was also investigated in previous studies. The degree of awareness to OC according to gender in previous questionnaire-based surveys showed no significant differences between males and females [26,27], which is consistent with the results of our study. Similarly, the same consistency was observed between responses of the current survey with other studies in relation to age [26,27], i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Oral cancer is defined as cancers arising on the lip, oral cavity, and oropharynx and it has been estimated that changes in the world's demography would result in an increase of incidence rates of oral cancer by 62% in 2035 (18,19). Consumption of cigarettes with high concentrations of alcohol increases the risk of oral cancer 6-15 times in people over 50 years of age (20).…”
Section: Discussionmentioning
confidence: 99%
“…al. (18), investigated the awareness of oral cancer among adults in Jakarta and a previously-tested questionnaire on 1000 adults in Jakarta was used in their study. They reported that only 53.2% of participants were aware of oral cancer and all of the smoker adults knew that tobacco increased the risk for oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…New prospects in oral precancer / cancer prevention associated with patient's mastering of the technique for oral cancer self-screening. The recent years studies indicate the general lack of oral cancer awareness and knowledge the out-patient population in the list of top oncological problems, crucial for prevention and early detection of precancer and cancer of the mouth [32][33][34][35][36][37][38][39][40][41]. A small number of publications have been dedicated to the assessment of oral cancer awareness in high risk patientsalcohol abusers, heavy smokers etc.…”
Section: Introductionmentioning
confidence: 99%